PERAN MA’RUF AMIN DALAM MERAIH SUARA MASYARAKAT MUSLIM PADA PEMILIHAN PRESIDEN 2019 - Sanusi, Ahmad; Gumilar, Galih (IAIN Samarinda, 2019)
The appointment of Ma’ruf Amin as Jokowi’s running mate in the presidential election of 2019 resulted in pros and cons among political elites in the country. This paper, thus, aims at explaining the dynamic of political communication that allowed the appointment of Ma’ruf Amin as Jokowi’s running mate in the election. This paper concludes that Ma’ruf Amin has a unique political position among amny other potential running mates. As a senior ulama with records of political positions during his career, Ma’ruf Amin has the potential to boost votes for Jokowi in the upcoming election, especially from the traditional Muslim of Nahdatul Umala, the largest Muslim organisation in the country, and in the world. Moreover, by appointing Ma’ruf Amin, one of the highest rank ulamas in Nahdatul Ulama, Jokowi can get rid of the stigma of himself being not friendly to Islam as he has been target of black campaigns for years.Keywords: Indonesian Presidential Election, Ma’ruf Amin effect, and political communication.